Atypical presentation of necrobiosis lipoidica in a pediatric patient. Issue 1 (2nd December 2018) - Özkur, Ezgi; Hasçiçek, Seyhan Ö.; Altunay, İlknur Kıvanç
Abstract: Necrobiosis lipoidica (NL) is a rare chronic granulomatous inflammatory skin disease characterized by brownish‐red papules and yellowish plaques with atrophic centers, which usually affect the legs, bilaterally. The average age of onset is 30‐40 years, and there are very few reported cases of necrobiosis lipoidica in children. A nondiabetic girl aged 14 years presented to our clinic with a history of an asymptomatic, 7 × 5‐cm single red plaque over her back in the interscapular area, which had started 5 years ago. Her laboratory tests were normal. A histopathologic evaluation confirmed the diagnosis of NL, and local treatment with clobetasol propionate twice daily was administrated. The patient will be followed up to monitor plasma glucose levels and evaluation of the lesion. Herein, we report a pediatric patient without diabetes mellitus who had NL in an atypical location and review the literature in view of the clinical features, complications, and treatment regimens for NL in children.